Has the Screen Killed the Page? I polizieschi and the case of Montalbano - Rinaldi, Lucia (Spunti e Ricerche, 2016)
Nowadays, interchanges between written and visual texts are countless, as postmodernism, with its tendency to combine different forms of art, has fostered the development of a tighter interplay between literature and the media, above all television. It is within this context that the popularity of many television crime dramas, and especially of the recent adaptations of Camilleri detective novels as a television series, Il commissario Montalbano, must be interpreted: as an example of people’s continuing predilection for visual narratives, above all those related to crime.